Breeding System Diversification and Evolution in American Poa supersect. Homalopoa (Poaceae: Poeae: Poinae) - Giussani, Liliana Mónica (2016)
Background and Aims: Poa subgenus Poa supersect. Homalopoa has diversified extensively in the Americas. Over half of the species in the supersection are diclinous; most of these are from the New World, while a few are from South-East Asia. Diclinism in Homalopoa can be divided into three main types: gynomonoecism, gynodioecism and dioecism. Here the sampling of species of New World Homalopoa is expanded to date its origin and diversification in North and South America and examine the evolution and origin of the breeding system diversity. Methods: A total of 124 specimens were included in the matrix, of which 89 are species of Poa supersect. Homalopoa sections Acutifoliae, Anthochloa, Brizoides, Dasypoa, Dioicopoa, Dissanthelium, Homalopoa sensu lato (s.l.), Madropoa and Tovarochloa, and the informal Punapoa group. Bayesian and parsimony analyses were conducted on the data sets based on four markers: the nuclear ribosomal internal tanscribed spacer (ITS) and external transcribed spacer (ETS), and plastid trnT-L and trnL-F. Dating analyses were performed on a reduced Poa matrix and enlarged Poaceae outgroup to utilize fossils as calibration points. A relaxed Bayesian molecular clock method was used. Key Results: Hermaphroditism appears to be pleisiomorphic in the monophyletic Poa supersect. Homalopoa, which is suggested to have originated in Eurasia 8·4–4·2 million years ago (Mya). The ancestor of Poa supersect. Homalopoa radiated throughout the New World in the Late Miocene–Early Pliocene, with major lineages originating during the Pliocene to Pleistocene (5–2 Mya). Breeding systems are linked to geographic areas, showing an evolutionary pattern associated with different habitats. At least three major pathways from hermaphroditism to diclinism are inferred in New World Homalopoa: two leading to dioecism, one via gynodioecism in South America and another directly from hermaphroditism in North America, a result that needs to be checked with a broader sampling of diclinous species in North America. A third pathway leads from hermaphroditism to gynomonoecism in Andean species of South America, with strictly pistillate species evolving in the highest altitudes. Conclusions: Divergence dating provides a temporal context to the evolution of breeding systems in New World Poa supersect. Homalopoa. The results are consistent with the infrageneric classification in part; monophyletic sections are confirmed, it is proposed to reclassify species of sect. Acutifoliae, Dasypoa and Homalopoa s.l. and it is acknowledged that revision of the infrageneric taxonomy of the gynomonoecious species is needed.